Premedication with salbutamol prior to surgery does not decrease the risk of perioperative respiratory adverse events in school-aged children - Ramgolam, A.; Hall, Graham; Sommerfield, D.; Slevin, L.; Drake-Brockman, T.; Zhang, G.; von Ungern-Sternberg, B. (Oxford University Press, 2017)
Background: Perioperative respiratory adverse events (PRAE) remain the leading cause of morbidity and mortality in the paediatric population. This double-blinded randomized control trial investigated whether inhaled salbutamol premedication decreased the occurrence of PRAE in children identified as being at high risk of PRAE. Methods: Children with at least two parentally reported risk factors for PRAE undergoing elective surgery were eligible for recruitment. They were randomized to receive either salbutamol (200 µg) or placebo prior to their surgery and PRAE (bronchospasm, laryngospasm, airway obstruction, desaturation, coughing and stridor) were recorded. Results: Out of 470 children (6–16 yr, 277 males, 59%) recruited, 462 were available for an intention-to-treat analysis. Thirty-two (14%) and 27 (12%) children from the placebo and salbutamol groups experienced PRAE. This difference was not significant [odds ratio (OR): 0.83, 95% confidence interval (CI): 0.48–1.44, P: 0.51]. Oxygen desaturation [14/232 (6%) vs 14/230 (6%), OR: 1.01, 95% CI: 0.47–2.17, P: 0.98] and severe coughing [12/232 (5%) vs 10/230 (4%), OR: 0.83, 95% CI: 0.35–1.97, P: 0.68] were the most common PRAE, but did not significantly differ between the groups. The occurrence of PRAE was slightly lower in children with respiratory symptoms who received salbutamol compared with placebo [16/134 (12%) vs 21/142 (15%), OR: 0.93, 95% CI: 0.38–2.26, P: 0.87], but was not significantly different. Conclusions: Premedication with salbutamol to children aged between 6 and 16 years and at high risk of PRAE prior to their surgery did not reduce their risk of PRAE. Trial registration number: ACTRN12612000626864 (www.anzctr.org.au).